2020
DOI: 10.7759/cureus.6918
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Mass: Two Case Reports of Rare Cesarean Scar Endometriosis

Abstract: Scar endometriosis is an uncommon type of extra-pelvic endometriosis. However, it should be suspected in any woman of childbearing age complaining of a cyclic, painful nodule in a scar from a previous obstetric or gynecologic procedure, after excluding other differential diagnoses. The treatment of choice is surgical resection. We report two cases of scar endometriosis that appeared in two young ladies after cesarean sections, discovered by a parietal mass near the cesarean scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Imaging studies like ultrasonography, MRI and CT scan can be useful to study the depth and extent of lesions to plan surgery 7,9 . Ultrasound is usually the first imaging technique used to study the identified mass on the abdominal scar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging studies like ultrasonography, MRI and CT scan can be useful to study the depth and extent of lesions to plan surgery 7,9 . Ultrasound is usually the first imaging technique used to study the identified mass on the abdominal scar.…”
Section: Discussionmentioning
confidence: 99%
“…Since scar endometriosis is known to develop following iatrogenic implantation of endometrial tissue during caesarean section, we believe that standardization of the techniques of caesarean section would reduce its incidence. Some of the standard good surgical techniques to be employed includes suturing of uterine incision without involving endometrium, using different sponges for cleaning the endometrium and the abdominal wound during caesarean section, using separate needles to close the uterine and abdominal wound, and thorough irrigation and cleaning of abdominal wound prior to closure 7,9,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is usually delayed because the signs and symptoms are not specific, and cyclic abdominal pain is not a pathognomonic sign for scar endometriosis. The differential diagnosis should be made with granuloma, desmoid tumor, lipoma, abscesses, sebaceous cysts, ventral hernias, or metastasis [ 7 ]. In our cases, the diagnosis was delayed around 2–3 years even if in the first case the pain has appeared 3 months after C-section.…”
Section: Discussionmentioning
confidence: 99%
“…Scar endometriosis is a rare form of endometriosis that typically occurs after gynecological or obstetric procedures such as caesarean sections, various laparoscopic procedures that require uterine cavity manipulation, needle tract amniocenteses, or perineal episiotomies [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis at a scar site can be found after caesarean section, hysterectomies, amniocentesis, laparoscopic trocar tracts, or perineal episiotomy. The most frequent localization of endometriosis in surgical scars is in the abdominal skin and subcutaneous tissue [4] . Furthermore, this disease is also related to surgery performed by general surgeons, such as appendectomy, groin and umbilical hernia corrections.…”
Section: Introductionmentioning
confidence: 99%